2019
DOI: 10.1002/dev.21826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early life NICU stress on the developing gut microbiome

Abstract: Succession of gut microbial community structure for newborns is highly influenced by early life factors. Many preterm infants cared for in the NICU are exposed to parent–infant separation, stress, and pain from medical care procedures. The purpose of the study was to investigate the impact of early life stress on the trajectory of gut microbial structure. Stool samples from very preterm infants were collected weekly for 6 weeks. NICU stress exposure data were collected daily for 6 weeks. V4 region of the 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 77 publications
0
42
0
1
Order By: Relevance
“…Environmental factors after birth, such as hospitalization, antibiotic usage, or diet, further modulate the development of the infant’s microbiome and immune system. Exposure to a variety of microbial organisms during early life appears to exert a protective effect [ 81 , 82 ]. The commensal bacteria may be involved in the development of lymphoid structures in the GI tract, such as Peyer’s patches and isolated lymphoid follicles, the promotion of intestinal epithelial cells (IECs), and the development of GI mucosal angiogenesis [ 83 , 84 , 85 ].…”
Section: Early Gut Microbiota and Immunitymentioning
confidence: 99%
“…Environmental factors after birth, such as hospitalization, antibiotic usage, or diet, further modulate the development of the infant’s microbiome and immune system. Exposure to a variety of microbial organisms during early life appears to exert a protective effect [ 81 , 82 ]. The commensal bacteria may be involved in the development of lymphoid structures in the GI tract, such as Peyer’s patches and isolated lymphoid follicles, the promotion of intestinal epithelial cells (IECs), and the development of GI mucosal angiogenesis [ 83 , 84 , 85 ].…”
Section: Early Gut Microbiota and Immunitymentioning
confidence: 99%
“…Very preterm infants are a unique population in that they are “new” from an evolutionary standpoint, have prolonged hospital stays (with multiple environmental exposures), are frequently exposed to antibiotics, and have immature innate and adaptive immune systems. In very preterm infants, the primary determinants of the composition of the intestinal microbiota are the post-menstrual age and age in weeks [ 34 , 35 ], however, multiple other factors are also influential including antenatal corticosteroids, mode of delivery, antibiotic exposure, feeding type, feeding tube dwell time and biofilms, gender, and stress [ 58 61 ]. Table 1 presents several examples of alterations in the infant fecal microbiota related to perinatal exposures [ 43 , 47 49 , 56 , 57 , 60 , 62 67 ].…”
Section: Causes Of Neonatal Intestinal Dysbiosismentioning
confidence: 99%
“…These observations in humans are reflected in experimental animal models of early-life stress, which have long been used to model both psychological and gastrointestinal disorders (O'Mahony et al, 2011). Moreover, a number of recent studies have demonstrated links between prenatal stress (including maternal anxiety) or early-life adversity (i.e., postnatal stress) and alterations in the human microbiota across the life span (Callaghan et al, in press;D'Agata et al, 2019;Hantsoo et al, 2019;Hemmings et al, 2017;Hu et al, 2019;Labus et al, 2017;Michels et al, 2019;Zijlmans et al, 2015).…”
Section: Box 1 Measuring the Microbiotamentioning
confidence: 99%